The Art of Translating Similes in the Works of Central Asian Writers - et. al., Nasiba Iskanova Parmonovna, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The topic is translating some stylistic devices in both English and Uzbek in order to develop sociocultural communicative competence and integrated skills of language learners. This article provides a brief overview of these approaches as well as methods for translating them. Some examples of simile from well-known writers' literary works are also provided here.